Current sedation practices for non-invasive procedures in tertiary maternity and children's hospitals in China: a 5-year update - Bo Li; Ruidong Zhang; Yanhui Huang; Mazhong Zhang; Jijian Zheng (BMJ Publishing Group, 2024)
Background Sedation techniques can ease anxiety during medical procedures for children. Our previous report on Chinese sedation practices for non-invasive procedures in 2018 is outdated due to the rapid development of sedation services. This study provides an updated report on sedation practices for non-invasive procedures in China.Methods This is a cross-sectional study. Questionnaires were sent to tertiary maternity and children's hospitals nationwide through the WeChat Mini Program. The survey questioned the location and caseloads of hospitals providing sedation services, support facilities, contraindications, fasting practices, sedation regimens, monitoring practices, staff structure, certification requirements for sedation providers and quality control data.Results Procedural sedation for non-invasive procedures were provided in 88 of 114 hospitals. These hospitals are located across the country except Heilongjiang province and the Tibet Autonomous Region. Compared with previous reports, significant increases were found in the number of hospitals providing sedation services, dedicated sedation rooms and recovery rooms and full-time sedation providers. Most hospitals advocated the 2-4-6 rule for pre-sedation fasting. Dexmedetomidine was the most used first-choice sedative. Anaesthesiologists remain the primary sedation providers, but nurses are also important. The most mentioned qualification requirements for sedation providers were a professional title of attending doctor, ≥5 years of working experience in paediatric anaesthesia and paediatric advanced life support certification. Sedation service records were used in 83 hospitals, but only 42 and 39 recorded success rates and adverse events, respectively.Conclusions Sedation services for non-invasive procedures are available in most areas of China. More hospitals now provide sedation services and full-time sedation providers. Supporting facilities and sedation regimens have improved. Non-anaesthesiologist sedation providers are important at current stage, developing training programmes for them may be necessary. Attention should be focused on quality control and improvement of sedation services.